Empowerment of Sigi Regency Community Human Resources through the LIREPDA Work Program by Islamic Relief - Poku, Dikson Nopriyanto; Rosanti, Ni Luh Putu Evvy; Wirastuti, Wiri; Palawa, Muh. Riswandi (Journal of Humanities, Community Service, and Empowerment, 2024)
This research investigates the empowerment of human resources implemented by Islamic Relief through the Lirepda (Livelihood recovery in the post-disaster area) program as a response to the earthquake's impact. The main objective of this research is to analyze the empowerment of human resources in the Sigi Regency carried out by Islamic Relief and its impact on economic recovery in disaster-affected areas. The research method used is descriptive with a qualitative approach. The research results show that Islamic Relief has empowered human resources through the Lirepda program for post-disaster economic recovery by providing skills training, business assistance, and distributing aid funds. Islamic Relief has succeeded in empowering existing human resources despite still needing to be implemented. The impact of this program is the restoration of livelihoods and positive changes in social conditions in society. Further analysis revealed factors influencing the program's success, including active community participation, cooperation with related parties, and full support from the government. This research provides insight into the important contribution of human resource empowerment in post-disaster economic recovery. It contributes to understanding how institutions such as Islamic Relief can effectively overcome challenges in the context of natural disasters.